GLP-1 Receptor Agonists: A Promising Therapy for Modern Lifestyle Diseases with Unforeseen Challenges - Patrycja Kupnicka; Małgorzata Król; Justyna Żychowska; Ryszard Łagowski; Eryk Prajwos; Anna Surówka; Dariusz Chlubek (MDPI AG, 2024)
Modern lifestyle diseases remain a persistent challenge in healthcare. Currently, about 422 million people worldwide are affected by diabetes, while 1 in 8 people are living with obesity. The development of glucagon-like peptide 1 receptor agonists (GLP-1RAs) has marked a significant milestone in treating these conditions. Interest in GLP-1RAs has grown due to evidence that, beyond their established role in diabetes management, these drugs influence other metabolic disorders. This is attributed to the fact that GLP-1 receptors are found in various healthy human tissues. However, a potential cause for concern is the expression of GLP-1 receptors in certain cancers. This review focuses on the most recent findings concerning the actions of GLP-1RAs, detailing their documented impact on the thyroid gland and pancreas. It addresses concerns about the long-term use of GLP-1RAs in relation to the development of pancreatitis, pancreatic cancer, and thyroid neoplasms by exploring the mechanisms and long-term effects in different patient subgroups and including data not discussed previously. This review was conducted through an examination of the literature available in the MedLine (PubMed) database, covering publications from 1978 to 10 May 2024. The collected articles were selected based on their relevance to studies of GLP-1 agonists and their effects on the pancreas and thyroid and assessed to meet the established inclusion criteria. The revised papers suggest that prolonged use of GLP-1RA could contribute to the formation of thyroid tumors and may increase the risk of acute inflammatory conditions such as pancreatitis, particularly in high-risk patients. Therefore, physicians should advise patients on the need for more frequent and detailed follow-ups.